Application of K-Means Clustering Data Mining in the Extension of the Contract of Work at PT. Afixkogyo Indonesia - Austin Almayda; Sudin Saepudin (Institute of Computer Science (IOCS), 2021)
Employment Contract/Employment Agreement according to Law No.13/2003 concerning Manpower is an agreement between a worker/labourer and an entrepreneur or employer that contains the terms of employment, rights and obligations of the parties. The omnibus law on employment, revised the provisions of the PKWT (certain time work agreement) in Law No. 13 of 2003 through amendments, deletions and additions to articles. However, the rules regarding contract employees are only described in outline in the Job Creation Law No. 11 of 2020. The law stipulates the maximum period of time for companies to carry out PKWT contracts for a maximum of 5 years.[1] The purpose of this study is to assist superiors or personnel in assessing contract employees in the company Pt.Afixkogyo Indonesia based on the results of employee assessments or the needs of the company itself. In the selection process for contract employees at Pt. Afixkogyo Indonesia is still using manual assessment in the field where the assessment of its employees is assessed by the head of the department, the purpose of this study is to apply and evaluate the Data Mining Clustering method to get an extension of the work contract at this company. The author uses one of the data mining methods Clustering/clustering because this method is very common in use so it is easy to implement because it uses simple principles that can be explained in non-statistical terms.